2018
DOI: 10.1101/438622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mindfulness meditators do not show differences in electrophysiological measures of error processing

Abstract: Mindfulness meditation may improve attention and self-regulation. One component of attention and self-regulation that may allow these improvements is performance monitoring. Neural correlates of performance monitoring can be objectively measured with electroencephalogram (EEG) via the error related negativity (ERN) and error positivity (Pe). Previous research assessing the ERN and Pe in meditators has resulted in inconsistent findings; some have reported alteration in peak amplitudes from both very brief medit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Similarly, the current results do not indicate meditation ubiquitously improves cognitive function (nor can the results answer the question of whether meditation only affects attention, or affects WM independently of attention, discussed further in the supplementary materials). Some of our research has shown null results in different measures of cognition (Bailey et al, 2018; J. Payne et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Similarly, the current results do not indicate meditation ubiquitously improves cognitive function (nor can the results answer the question of whether meditation only affects attention, or affects WM independently of attention, discussed further in the supplementary materials). Some of our research has shown null results in different measures of cognition (Bailey et al, 2018; J. Payne et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
“…Finally, we feel it is important to note that the current results require replication before we can be confident they reflect true differences between meditators and non-meditators. Typically this point is taken for granted in scientific research, but we think it is worth noting explicitly given the current replication crisis in psychology (Collaboration, 2015), recent non replications in mindfulness research (Bailey et al, 2018; J. Payne et al, 2019), and the current media hype surrounding mindfulness research.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies suggest that meditators possess superior conflict monitoring abilities. Although convincing, it is important to note that a more recent study, which used novel whole-scalp EEG analysis, reported no behavioral or neural differences between meditators and controls (Bailey, Freedman, Fitzgibbon, Rogasch, Van Dam, & Fitzgerald, 2019). A final note is that although mindfulness skill has primarily been estimated cross-sectionally, and typically based on self-reported hours of practice, efforts are underway to derive performance-based measures of mindfulness skills with adequate psychometric properties, such that these can be utilized as alternative means of skill assessment in experimental designs (Levinson, Stoll, Kindy, Merry, & Davidson, 2014;Hadash & Bernstein, 2019).…”
Section: Mindfulness Skillmentioning
confidence: 96%
“…Furthermore, across all participants (e.g., both mindful and controls), higher acceptance was correlated with a more negative ERN . Bailey et al (2018) attempted to replicate these findings but found no differences in the ERN between meditators of two or more years with a comparative control group.…”
mentioning
confidence: 98%